The Resistance to the Hegemony of Power in Di Kaki Bukit Cibalak Novel by Ahmad Tohari - Musa, Musa; Supriyanto, Teguh; Doyin, Mukh (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
In a literature, the hegemony of power is frequently occurred in leadership activity. It was also occurred in a novel of Ahmad Tohari entitled Di Kaki Bukit Cibalak focused on ruler’s injustice as a social problem. The novel talked about a movement to demolish the hegemonic power. The aim of the study was to describe a form of resistance to hegemony and in what kind of society the hegemony power occurred written in Di Kaki Bukit Cibalak novel. The method of the study was semiotic by using several approaches: heuristic, hermeneutic, and sociology of literature. There were five forms of hegemony namely: hegemony to assets, hegemony to citizens, hegemony of intellectuals, hegemony of shamans to their patients, and hegemony to Chinese descendants. In terms of resistance to hegemony, it was happened the resistance through shaman and media. The resistance to hegemony of power occurred in a proletar – bourgeois society and capitalist – intellectual society.